Analisis Faktor Karakteristik Perawat yang Berhubungan dengan Respon Time: Uji Korelasi - Fitri Suciana; Ana Rizkianti; Esri Rusminingsih; Agung Kristanto (Universitas Muhammadiyah Klaten, 2025)
Emergency response time (response time) is very important in the emergency room to determine the next step. Response time is the response of medical personnel in handling patients from the time the patient arrives to get service and is completed within 5 minutes. The purpose of this study was to determine whether there was a correlation between the characteristics of nurses and response time so that the research design used ainailitik suirvey with pendekaitain yaing diguinaikain cross sectionail, The sample in the study were emergency room nurses who were not on major leave and willing to be respondents using a total sampling technique of 30 respondents. Instruments using questionnaires and observation sheets. The results showed that the majority of respondents were male by 62.1%, most of the last education was Diploma of Nursing by 65.5%, the majority of respondents had a work period of more than 3 years by 96.6%, workload with a percentage of 51.7%, response time with a fast category of 75.9. The results of the correlation test obtained from several characteristics that have a relationship are skills with workload with a P value of 0.00 and age with workload with a P value of 0.00. The conclusion is that there is a relationship between nurse characteristic factors with skill and age factors, and there is no relationship between nurse characteristic factors with response time including, gender, workload, tenure, education.